Isolation, identification, characterization and phylogenetic analysis of Leptospira serovars in rats trapped in selected areas of Kuala Lumpur, Malaysia - Hasoun, Ghada A. (2017)
Leptospirosis is a global zoonotic disease of humans and a wide range of domestic animals caused by pathogenic species of Leptospira. The genusLeptospira comprises 20 species; nine of them are pathogenic, five species as intermediate and the last six species as saprophytes. DNA-Based methods were used for classification of Leptospira besides, the use of Polymerase chain reaction assay (PCR) as an unconventional tool for identification and characterization. Leptospirosis has a significant impact on public health and livestock production. Rodents, particularly rats, have been described as the main source of infection to humans and animals. The importance of leptospirosis is that it is a zoonosis and a public health concern. It is also of great economic impact in Malaysia, since almost all rats are infected with Leptospira spp. and they shed the pathogenic leptospires to the environment, subsequently infecting humans and animals within the same zone. Conversely, there is not abundant evidence available about the renal carriage in rats from urban areas in Kuala Lumpur. That influences us towards finding new molecular approaches for early detection and diagnosis of the infection particularly through sensitive, specific and rapid molecular methods. Prevalence of leptospirosis in rat populations from urban areas has been studied in this project through implementing molecular and classical techniques. The association between rat categories through Pearson Chi square and the agreement between results of tests through Cohen Kappa analysis were done in addition to identifying the predominant rat species which carry and disseminate the infection in the studied locations. In this study, 112 rats were trapped and sacrificed from four locations (wet markets) in Kuala Lumpur, Malaysia where the poor hygiene renders the probability of infected rats with leptospirosis possible. Sera and both kidneys of each rat were collected and categorized by; species, gender and age which were studied. Serological and molecular detection were performed, using microscopic agglutination test (MAT) for anti-Leptospira anti-body detection in sera against 18 standard Leptospira strains and multiplex polymerase chain reaction (mPCR) for direct detection of Leptospira DNA in rat kidney tissues. Each test was evaluated with respect to its sensitivity and specificity ensuring that the recommendations made are valid to be used in a program for leptospirosis eradication in the country. Isolation of the Leptospira isolates from culturing of rat kidney tissues in a selective medium (EMJH) and then characterization and identification by classical and molecular methods were also done. Molecular characterization of recovered Leptospira isolates was achieved by PCR-Restriction fragment length polymorphism (PCR-RFLP) through digestion of PCR products amplified with lipL32 (819bp) and 16S rRNA (541bp) with restriction enzymes Bam HI and KpnI respectively. Besides, constructing the tree for phylogenetic analysis of the obtained isolates by sequencing the lipL32 (819bp) region and 16S rRNA (541bp) region and the genetic relationships were determined. The MAT revealed 8 serovars infected 63/112 of the sampled rats; L. borgpetersenii serovars Javanica and L. interrogans serovars; Bataviae, Icterohaemorrhagiae, Canicola, Pomona, Australis, Andamana and Patoc. While, mPCR showed 56 DNA samples were positive to both genes (16S rRNA,lipL32 genes) and only 4 DNA samples positive to 16S rRNA. Study of seroprevalence association based on the mentioned categories revealed that; Rattusrattus and Rattusnorvegicus were the predominant rat species with no statistical significance (χ2 = 0.490a; P=0. 484) between both species. Though infected males of rats were more infected than females, (χ2 = 1.765a; P=0. 184), this was not statistically significant. Adult infected rats were more than sub adults and the difference was statistically significant (χ2 = 6.748a; P=0.009). Cultures of the tissues from rat kidneys were examined by dark field microscopy and found 57/ 112 positive. Identification of the isolates using 8-azaguanine, 1M NaCl and Trypticase soy broth indicated 40 Leptospiraisolates were pathogenic whereas, 17 Leptospira isolates were non-pathogenic. Detection of Leptospira DNA in 112 kidney cultures by PCR showed 50 isolates were pathogenic and positive to PCR-lipL21 and G1/G2 genes. The sensitivity of isolation was 70.2% in comparison with PCR whilst, the specificity was 81.8%. Typing of isolates by MAT against 16 rabbit hyperimmune anti sera revealed 13/57 isolates belong to L. interrogans serovar Bataviae and 17/57 were serovar Javanica belonging to L. Borgpetersenii. Characterization of isolates by Restriction fragment length poly morphism PCR-RFLP of lipL32 (819 bp) generated two different patterns on agarose gel that differentiated between L. interrogans and L. borgpetersenii species. On the other hand, phylogenetic analysis showed horizontal transfer of ribosomal gene through sequencing the 16S rRNA gene in serovar Hardjo belonging to both pathogenic Leptospira species. Sequencing of lipL32 gene showed the genetic nature of isolates that belonged to L. interrogans and L. borgpetersenii spp. but different in serovars which was revealed by MAT. Combinations of serologic analysis namely MAT and the DNA-based methods particularly PCR and mPCR (16S rRNA,lipL32 genes) showed promising results. This combination can be used for rapid, sensitive detection of leptospirosis in humans and animals. Assays of recovered isolates with PCR-RFLP of lipL32 is valuable for discriminatory needs. Phylogenetic analysis is decisive in findings of isolate relationships and heterogeneity among serovars circulated in the rat populations. It appears that leptospirosis is endemic in Malaysia and rats are the main source of infection. Although multi-approaches are needed for detection and characterization of Leptospira spp., PCR-based methods are rapid, sensitive and accurate. Further studies using advanced molecular methods are required for early detection and diagnosis of leptospirosis.